Country of birth modifies the association of fatty liver index with insulin action in Middle Eastern immigrants to Sweden. Issue 1 (October 2015) - Bennet, Louise; Groop, Leif; Franks, Paul W.
Highlights: Non-alcohol fatty liver disease (NAFLD) is a strong risk factor for type 2 diabetes. The prevalence of NAFLD varies across populations of different ethnic backgrounds but the prevalence in Middle Eastern populations, which are at high risk of type 2 diabetes, is largely unknown. We investigated fatty liver index (FLI), an estimate of NAFLD. Further we calculated the odds of NAFLD (FLI ≥ 70) given country of origin and also studied associations between insulin sensitivity index (ISI) and FLI. Furthermore, high FLI and Iraqi origin were independently associated with impaired insulin action irrespective of traditional risk factors such as physical inactivity, abdominal obesity and type 2 diabetes. The finding that country of birth modifies the relationship of FLI with ISI, suggests a stronger effect of fatty liver on insulin action in Iraqis than in Swedes, and opens a possible effect of fatty liver as a cause of impaired insulin action and increased risk of type 2 diabetes in this population that to our knowledge has not been reported before. Abstract: Aims: Non-alcohol fatty liver disease (NAFLD) is a strong risk factor for insulin resistance and type 2 diabetes. The prevalence of NAFLD varies across populations of different ethnic backgrounds but the prevalence in Middle Eastern populations, which are at high risk of type 2 diabetes, is largely unknown. Using fatty liver index (FLI) as a proxy for NAFLD the aim was to calculate the odds of NAFLD (FLI ≥ 70) given country of origin and further to investigate the associations between ISI and FLI. Methods: In 2010–2012 we conducted a population-based study of individuals aged 30–75 years born in Iraq or Sweden, in whom anthropometrics, fasting blood samples and oral glucose tolerance tests were performed and sociodemography and lifestyle behaviors characterized. Results: A higher proportion of Iraqis ( N  = 1085) than Swedes ( N  = 605) had a high probability of NAFLD (FLI ≥ 70, 32.5 vs. 22.6%, p  < 0.001, age- and sex-adjusted data) and ISI was more severely impaired (70.7 vs. 95.9%, p  < 0.001). Independently of traditional risk factors for NAFLD, being born in Iraqi increased the risk of FLI ≥ 70 (OR 1.59: 95% CI 1.15, 2.20). Furthermore, country of birth presented a stronger association between ISI and FLI ≥ 70 in Iraqis than in Swedes ( P interaction  = 0.019). Conclusions: Our data indicate that immigrants from Iraq are at higher risk of NAFLD. The finding that country of birth modifies the relationship of FLI with ISI, suggests that liver fat may be a stronger determinant of impaired insulin action and increased risk of type 2 diabetes in Iraqis than in Swedes.